2022
DOI: 10.1111/jpy.13244
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation Influenced by Phosphorus and Nitrogen Availability in the Benthic Bloom‐forming Cyanobacterium Hydrocoleum sp. Identified in a Temperate Marine Lagoon

Abstract: The nitrogen‐fixing, non‐heterocystous cyanobacterium Hydrocoleum sp. (Oscillatoriales) is a common epiphytic and benthic bloom‐former in tropical and subtropical shallow water systems but shares high phylogenetic similarity with the planktonic, globally important diazotroph Trichodesmium. Multiphasic observations in this study resulted in unexpected identification of Hydrocoleum sp. in mass accumulations in a coastal lagoon in the Western temperate North Atlantic Ocean. Hydrocoleum physiology was examined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Biological N 2 -fixation is a highly energy-consuming biochemical process. When the available N in environment meets the demand of diazotrophic microorganisms, they prefer to reduce the activity of nitrogenase and directly absorb available N like NH + 4 from environment (Moisander et al, 2022). Numerous studies showed that NH + 4 addition inhibited the activity of nitrogenase of diazotrophic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Biological N 2 -fixation is a highly energy-consuming biochemical process. When the available N in environment meets the demand of diazotrophic microorganisms, they prefer to reduce the activity of nitrogenase and directly absorb available N like NH + 4 from environment (Moisander et al, 2022). Numerous studies showed that NH + 4 addition inhibited the activity of nitrogenase of diazotrophic microorganisms.…”
Section: Discussionmentioning
confidence: 99%